REFLEKSI SOSIAL NOVEL MEI MERAH 1998: KALA ARWAH BERKISAH KARYA NANING PRANOTO (KAJIAN SOSIOLOGI SASTRA ALAN SWINGEWOOD) - Sunarti, Sunarti; Tang, Muhammad Rapi; Nensilianti, Nensilianti (Fakultas Bahasa dan Sastra Indoensia, 2021)
This study aims to describe phrases, sentences, or paragraphs that describe social reflections and reflections of the times contained in the novel Mei Merah 1998: Kala Arwah Berkisah by Naning Pranoto using the study of sociology of literature by Alan Swingewood. This research is qualitative. The data in this study were obtained by the case study method. The source of the data was obtained by reading the novel Mei Merah 1998: Kala Arwah by Naning Pranoto. The results of this study are forms of social reflection and reflection of the times that describe social phenomena that occurred during the reformation period where there were rebellions and looting and rape committed by demonstrators.